English Vocabulary Achievement Through Telling Stories Using Pictures in Islamic Elementary School - Aminulloh Aminulloh; Asropi Safi'i; Muhammad Eka Rahman (Universitas Muhammadiyah Sidoarjo, 2019)
This reserch focuses on English vocabulary achievement through telling stories Using pictures. The general problem of this research is How far is the English vocabulary achievement through telling stories using pictures of the fifth year student of MIMA KH Siddiq Jember?